Characterization of 16S rRNA of the gut microbiome in long-tailed macaque (Macaca fascicularis) with spontaneous type 2 diabetes mellitus - PRAMESTY WULAN RAMADHANTY; UUS SAEPULOH; IRMA HERAWATI SUPARTO; HUDA SHALAHUDIN DARUSMAN (Society for Indonesian Biodiversity, 2023)
Abstract. Ramadhanty PW, Saepuloh U, Suparto IH, Darusman HS. 2023. Characterization of 16S rRNA of the gut microbiome in long-tailed macaque (Macaca fascicularis) with spontaneous type 2 diabetes mellitus. Biodiversitas 24: 6191-6199. The gut microbiota in the body is very complex and varied. It is known to influence human health. Imbalance (dysbiosis) of the gut microbiota can lead to type 2 diabetes mellitus (T2DM) and become a new feature in the development of the disease. Several human studies have compared the bacterial community in T2DM and non-T2DM patients. Until now, research on gut microbiota associated with T2DM in non-human primate animal models is still rare. T2DM can be developed by long-tailed macaque with clinical features similar to humans, which provides important information about the relationship between gut microbiota and T2DM. This study aims to characterize full-length 16S rRNA genes to obtain gut microbiota profiles in long-tailed macaques with and without spontaneous T2DM. The characterization was carried out using a metagenomic approach targeted at the full-length 16S rRNA gene with Nanopore technology (GridION) as one of the third-generation sequencing. The sample used was rectal swabs from adult male long-tailed macaques in the spontaneous T2DM group (n=3) and non-T2DM group (n=3). An increase in the alpha diversity, Firmicutes phylum, Oscillibacter genus, Oscillibacter valericigenes, and Oscillibacter ruminantium species, as well as a decrease in the Proteobacteria phylum were found in the T2DM group. The Firmicutes/Bacteroidetes ratio was also increased in the T2DM group compared to the non-T2DM group, which indicates dysbiosis. Based on these results, the metagenomic marker of the gut microbiome T2DM was obtained in long-tailed macaque primates, similar to humans with T2DM.